2001
DOI: 10.1046/j.1365-2036.2001.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole 20 mg maintains symptom control in endoscopy‐negative gastro‐oesophageal reflux disease: a controlled trial of ‘on‐demand’ therapy for 6 months

Abstract: Background: Most patients with gastro‐oesophageal reflux disease (GERD), regardless of endoscopic status, suffer symptomatic relapse within 6 months of stopping acid suppressant therapy. Aim: To assess the efficacy of ‘on‐demand’ treatment of GERD with esomeprazole, the first proton pump inhibitor developed as an optical isomer. Methods: In this multicentre, double‐blind study, 342 endoscopy‐negative GERD patients demonstrating complete resolution of heartburn during the final week of a 4‐week treatment period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
3
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(184 citation statements)
references
References 19 publications
10
165
3
6
Order By: Relevance
“…On-demand treatment may be more acceptable to patients than the requirement to take medication every day on a long-term basis [10] . In placebo-controlled trials, esomeprazole 20 mg on demand has been shown to be effective and well tolerated in the maintenance of symptom control in patients with NERD [18,19] . In the present study, more patients discontinued from the 8-wk than the 2-wk treatment arm, which may have been the result of the different drug exposures in the treatment period and the difference in assigning maintenance/on-demand treatment in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…On-demand treatment may be more acceptable to patients than the requirement to take medication every day on a long-term basis [10] . In placebo-controlled trials, esomeprazole 20 mg on demand has been shown to be effective and well tolerated in the maintenance of symptom control in patients with NERD [18,19] . In the present study, more patients discontinued from the 8-wk than the 2-wk treatment arm, which may have been the result of the different drug exposures in the treatment period and the difference in assigning maintenance/on-demand treatment in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is increasing support for the on-demand approach as the preferred strategy. [10][11][12] For example, Bardhan et al prospectively enrolled 526 patients and treated them with either an H 2 RA or proton pump inhibitor taken as needed. 10 Approximately 50% of the patients did not need to take any acid-suppressive medication for a minimum of 6 of the 12 months of the study.…”
Section: Choice Of Strategymentioning
confidence: 99%
“…5 This definition includes ondemand (intermittent) users of PPI, who on average use 1 tablet or capsule of PPI every 3-4 days, equivalent to at least 120 tablets or capsule per year. 11,12 Because 90-day supplies may be dispensed in the VA clinic pharmacies or by mail order, longterm PPI users in the present study could include patients with as little as 1 dispensing.…”
Section: ■■ Methods Study Design and Patient Populationmentioning
confidence: 99%